Nitrogen Fertilizers Shape the Composition and Predicted Functions of the Microbiota of Field-Grown Tomato Plants - Caradonia, Federica; Ronga, Domenico; Catellani, Marcello; Azevedo, Cleber Vinicius Giaretta [UNESP]; Terrazas, Rodrigo Alegria; Robertson-Albertyn, Senga; Francia, Enrico; Bulgarelli, Davide (Amer Phytopathological Soc, 2019)
The microbial communities thriving at the root-soil interface have the potential to improve plant growth and sustainable crop production. Yet, how agricultural practices, such as the application of either mineral or organic nitrogen fertilizers, impact on the composition and functions of these communities remains to be fully elucidated. By deploying a two-pronged 16S rRNA gene sequencing and predictive metagenomics approach, we demonstrated that the bacterial microbiota of field-grown tomato (Solarium tycopersicum) plants is the product of a selective process that progressively differentiates between rhizosphere and root microhabitats. This process initiates as early as plants are in a nursery stage and it is then more marked at late developmental stages, in particular at harvest. This selection acts on both the bacterial relative abundances and phylogenetic assignments, with a bias for the enrichment members of the phylum Actinobacteria in the root compartment. Digestate-based and mineral-based nitrogen fertilizers trigger a distinct bacterial enrichment in both rhizosphere and root microhabitats. This compositional diversification mirrors a predicted functional diversification of the root-inhabiting communities, manifested predominantly by the differential enrichment of genes associated to ABC transporters and the two-component system. Together, our data suggest that the microbiota thriving at the tomato root soil interface is modulated by and in responses to the type of nitrogen fertilizer applied to the field.
Keywords: digestate; fertilizers; metagenomics; microbiota; nitrogen; rhizosphere and phyllosphere; root; Solanum lycopersicum; yield and crop productivity